ANALYSIS OF PROBLEM SOLVING MODELS IN ENGINEERING EDUCATION - Muhammad Baba Gusau, Nabila; Mohamad M.M (Online Journal for TVET Practitioners, 2018)
Engineering education emphases deeply on problem-solving, nevertheless several instructors impart content besides formerly assume learners to always solve problems deprived of being exposed the method involved. Our situation is that a strong analysis of problem-solving plans and problem-solving proposals must remain involved in each engineering gathering, Problem-solving is careful to be a vital movement of an engineering exercise, the writers analyzed some of the problem-solving models rummage-sale by engineering learners to solve problems that need continuously remained a portion of engineering teaching. Numerous of the new current problem-solving models described in the engineering education training are analysis, divided and related in this paper. This of Analysis indicated that Wankat & Oreovicz, the problem-solving model is overall sufficient to put up most of the essentials (but, not essentially completely) of the other models. As soon as correctly applied, this model likewise donates to the growth of the supplementary thinking skills, motivation skills, innovation and problem-solving skills required of engineering educationalists.